Usaha Guru Pendidikan Agama Islam Dalam Menangani Kenakalan Pada Siswa Kelas III Di UPT SD Negeri 019 Muara Uwai Bangkinang - Dahlia, Netti (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2022)
The aim of the research was to find out the forms of delinquency in class III students at SDN 019 Muara Uwai Bangkinang, Kampar Regency and the efforts of Islamic religious education teachers in dealing with student delinquency. This research is a field research (field research). The study involved third-grade Islamic Religious Education teachers and third-grade students at SD Negeri 019 Muara Uwai Bangkinang. Data collection techniques are carried out by observation, interviews, and documentation. The data analysis is descriptive qualitative, namely: data collection as well as data reduction, data presentation, and drawing conclusions. The results of the study can be concluded that the forms of student delinquency are: playing around in class, poorly managed, disturbing friends, mocking friends, cheating during exams or tests and seizing during class hours, talking dirty and fighting the teacher.